Kecakapan Abad 21: Kompetensi Digital Pendidik Masa Depan - Rayinda Dwi Prayogi (Universitas Muhammadiyah Surakarta, 2020)
This study aims to know about the 21st Century skills discourse comprehensively. Such knowledge is the basic capital of the educators' paradigm for developing students to be skilled in accordance with their times. Given the reality of educators who are reluctant to actually use technology that every child has been in and even capable of. This reluctance might be caused by technophobia, skepticism or other reasons. This research is qualitative research. The qualitative approach emphasizes its analysis of descriptive data. The data collected will be analyzed using descriptive analysis method which consists of three main activities, namely: data reduction, data presentation and drawing conclusions by exploring the deepest meaning systematically. The results of this study indicate that digital competence must be possessed by educators to present new content in 21st century learning. Digital competence is a new ability for educators in 21st century learning. Digital competence shows the use of information and communication technology based on pedagogical principles by realizing its implications for methodology education. The digital competencies include mastering information and communication, creating learning content, and solving educational problems